Arsenic removal using advanced reduction process with dithionite/UV—A kinetic study. (June 2018) - Kaushik, Vishakha; Duan, Yuhang; Jung, Bahngmi; Batchelor, Bill; Abdel-Wahab, Ahmed
Abstract: The paper describes the use of advanced reduction processes (ARPs) with dithionite/UV to remove arsenic from water/wastewater. The highly reducing radicals generated by the ARP react with arsenite and arsenate to produce solid phases such as elemental arsenic or arsenic sulfides that can be readily removed. This study evaluated the effectiveness in removing arsenic at 5 different pH values (5, 6, 7, 8, and 9) as well as the mechanism of resolubilization for solids. Moderate pH values of 6, 7, and 8 were found to be the most effective for arsenic removal. Resolubilization occurred at all pH values because dithionite was consumed under UV irradiation. A simple kinetic model was applied to describe the changes in concentrations of arsenic and dithionite with time. Arsenic removal kinetics was fast at the first 10–20 min for all pH values. The highest rate constant was observed at pH 6 for arsenate removal (616 L/mol/min) and at pH 7 for arsenite removal (534 L/mol/min).